Psychometric study of the differentiation of self scale-revised in a sample of Spanish adults - Oliver-Pece, Jesús; Jódar, Rafael; Berástegui Pedro-Viejo, Ana; Skowron, Elizabeth A.; Friedlander, Myrna L.; Schmitt, Thomas A. (Current Psychology, 2022)
This study analyzes the psychometric properties of the Diﬀerentiation of Self Scale-Revised (DSS-R), an instrument assess-ing the diﬀerentiation of the self of Spanish adults through the dimensions I Position, Emotional Reactivity, Fusion with Others and Emotional Cutoﬀ, and of a new dimension, Dominance over Others. In Study 1, carried out with 1445 subjects, exploratory factor analysis was performed with one half of the participants, and conﬁrmatory factor analysis with the other, comparing the ﬁve-factor and bifactor models. In Study 2, examining convergent validity, 180 subjects participated and completed the revised scale and the Diﬀerentiation of Self Inventory-Revised. Studies 3 and 4 veriﬁed concurrent validity, with 401 subjects completing the DSS-R and the State-Trait Anxiety Inventory in Study 3, and 170 subjects completing the DSS-R and the Couple Assertion Questionnaire in Study 4. Adequate internal consistency indices and evidence of construct, convergent and concurrent validity were found. The use of the DSS-R is recommended for assessing the diﬀerentiation of the self in the Spanish population.
Keywords: Identidad (Psicología); Psicometría; Diﬀerentiation of self; Scale; Psychometric analysis; Validity; Reliability